2020
DOI: 10.1186/s12866-020-01897-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcium regulates the mycophagous ability of Burkholderia gladioli strain NGJ1 in a type III secretion system-dependent manner

Abstract: Background: A rice associated bacterium Burkholderia gladioli strain NGJ1 demonstrates mycophagy, a phenomenon wherein bacteria feed on fungi. Previously, we have reported that NGJ1 utilizes type III secretion system (T3SS) to deliver a prophage tail-like protein (Bg_9562) into fungal cells to establish mycophagy. Results: In this study, we report that calcium ion concentration influences the mycophagous ability of NGJ1 on Rhizoctonia solani, an important fungal pathogen. The calcium limiting condition promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…We have previously reported that T3SS plays an important role during mycophagy, the T3SS mutant NGJ1 bacterium being completely defective in mycophagy (Swain et al ., 2017). The wild‐type NGJ1 deploys various T3SS effectors, including Bg_9562, a prophage tail‐like protein (Swain et al ., 2017), and endo‐β‐1, 3‐ glucanase (Yadav et al ., 2020) to potentially lyse fungal cells to feed on them. The data presented in the current study reflect that the expression of Bg_9562 , endo‐β‐1 , 3‐glucanase as well as T3SS apparatus ( hrcC and hrcN ) encoding genes are upregulated during mycophagous interaction of wild‐type NGJ1 with R. solani and the upregulation is dependent on RpoN1 and RpoN2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that T3SS plays an important role during mycophagy, the T3SS mutant NGJ1 bacterium being completely defective in mycophagy (Swain et al ., 2017). The wild‐type NGJ1 deploys various T3SS effectors, including Bg_9562, a prophage tail‐like protein (Swain et al ., 2017), and endo‐β‐1, 3‐ glucanase (Yadav et al ., 2020) to potentially lyse fungal cells to feed on them. The data presented in the current study reflect that the expression of Bg_9562 , endo‐β‐1 , 3‐glucanase as well as T3SS apparatus ( hrcC and hrcN ) encoding genes are upregulated during mycophagous interaction of wild‐type NGJ1 with R. solani and the upregulation is dependent on RpoN1 and RpoN2.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, we anticipate them to be under indirect regulation of RpoNs in NGJ1. This is further supported by our observation that rpoN1 and rpoN2 genes (upregulated during 24 h of mycophagous interaction) exhibit different temporal expression with that of T3SS genes (upregulated during 48 h, but not during 24 h of mycophagy interaction; Yadav et al ., 2020). In this regard, it is to be noted that RpoN modulates T3SS functions in Erwinia amylovora (a plant pathogenic bacteria) via regulation of HrpL (an alternative sigma factor; sigma 70), the master regulator of T3SS (Ancona et al ., 2014; Lee et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ca 2+ could influence the adhesion of Bacillus sp. presumably by regulating aggregation and formation of extracellular polymeric substances (He et al, 2016), changes in Ca 2+ concentration could affect pectinolytic enzyme production in Pectobacterium carotovorum and biofilm formation in Xylella fastidiosa (Flego et al, 1997;Parker et al, 2016); the swarming motility of Pseudomonas syringae grown on agar medium supplemented with Ca 2+ was reduced, due to the precipitation of calcium phosphate on the surface of cells (Fishman et al, 2018); and the mycophagous ability of Burkholderia gladioli strain NGJ1 against Rhizoctonia solani was regulated by Ca 2+ in a type III secretion system-dependent manner (Yadav et al, 2020). It has also been shown that Ca 2+ modulates bacterial gene expression (Fishman et al, 2018;Gode-Potratz et al, 2010), suggesting its regulatory properties.…”
Section: Introductionmentioning
confidence: 99%